Study on mid-term outcomes of atherectomy for patients with femoral popliteal artery lesions with different Global Limb Anatomic Staging System grades - Yue, Yanyu; Zhang, Youjia; Zhang, Liang; Gao, Zheng; Du, Xiaolong; Ran, Feng (PeerJ, 2024)
Objective To investigate the mid-term efficacy and patency rate of TurboHawk peripheral plaque excision system in the treatment of femoral popliteal artery lesions with different Global Limb Anatomic Staging System (GLASS) grades. Methods The clinical data of 141 patients with femoral popliteal arteriosclerosis obliterans who were treated with TurboHawk from January 2018 to July 2022 in our institution were retrospectively analyzed. There were 109 male patients and 32 female patients. Recordings were made of the patient’s symptoms of limb ischemia, technical success rate, primary patency rate of target vessels, ankle brachial index (ABI), GLASS grades, postoperative complications, and a statistical analysis with the patient’s preoperative treatment was conducted. Results All patients had improved limb ischemia symptoms to varying degrees after surgery, with a technical success rate of 100% (femoral artery puncture and superficial femoral artery recanalization) without bleeding, hematoma, pseudoaneurysm, arteriovenous fistula or other complications. The follow-up period was 1-24 months, during which the severity of claudication, resting pain, and toe ulcers significantly improved. The primary patency rate of the target vessel was 98.58% (139/141), and the ABI significantly increased on the second day, three months, and six months after surgery compared to before surgery. No major adverse events were found during follow-up. The patency rates at 1, 6, 12 and 24 months after intervention were 100%, 80%, 75% and 60% respectively. Conclusion The mid-term efficacy and patency rate of TurboHawk in the treatment of femoral popliteal artery lesions with GLASS I patients have the best mid-term prognosis, the highest mid-term survival rate, and the highest vascular patency. The plaque removal system has proven to be an effective treatment for individual localized chronic total occlusion lesions. Additionally, the TurboHawk system provides a safe and minimally invasive treatment alternative for superficial femoral artery conditions, achieving significant therapeutic results within a brief period.
Keywords: Atherectomy; Claudication; Critical limb ischemia; Turbohawk; Target lesion revascularization; Patency